2021
DOI: 10.1093/asj/sjab053
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Face and Neck lift: A Traditional Method With Definite Effects Among Asians

Abstract: Background The mainstream face lifts in western countries always involve the SMAS treatment. Meanwhile, subcutaneous face and neck lift is wildly applied among Asians. Objectives To evaluate outcomes of subcutaneous face and neck lift, including patient-reported and 3D measurement outcomes, and report on details of surgical procedures. Methods Patients who re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Meanwhile, our previous study using 3D imaging measurements suggested that this technique also improved the zygomatic volume and decreased the nasolabial and lateral cheek volume. 9 Facial fat is not homogeneous but rather a series of compartments separated by specific fibrous septa, which explains the compartment-specific deflation observed during aging. 10,11 Although a subcutaneous face and neck lift does not directly pull up the superficial fat similar to a SMAS-associated facelift, it helps relieve the appearance of sagging.…”
Section: Surgical Idea and Techniquementioning
confidence: 99%
“…Meanwhile, our previous study using 3D imaging measurements suggested that this technique also improved the zygomatic volume and decreased the nasolabial and lateral cheek volume. 9 Facial fat is not homogeneous but rather a series of compartments separated by specific fibrous septa, which explains the compartment-specific deflation observed during aging. 10,11 Although a subcutaneous face and neck lift does not directly pull up the superficial fat similar to a SMAS-associated facelift, it helps relieve the appearance of sagging.…”
Section: Surgical Idea and Techniquementioning
confidence: 99%
“…However, several possible mechanisms have been proposed. Among the most commonly cited hypotheses are genetic predisposition (i.e., DNMT3A, JAK-STAT3 pathway, and mutations in TP53), bacterial biofilm (BF), chronic inflammation, and digestion of particulate debris shed from textured breast implants [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of filler injection procedures for cosmetic and reconstructive purposes, it has become widely popular with patients seeking treatment for signs of aging with a quick return to daily life. 1–3…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of filler injection procedures for cosmetic and reconstructive purposes, it has become widely popular with patients seeking treatment for signs of aging with a quick return to daily life. [1][2][3] According to some authors, the negative reactions of permanent fillers are produced by a low-grade bacterial infection surrounding foreign substances. The development of related fibrosis is determined by the implant's physical attributes and inherent traits.…”
Section: Introductionmentioning
confidence: 99%